Subchondral Bone Condition and Intraoperative Grading of Cartilage Degeneration Underneath Patella Unrelated to the Clinical Outcome after TKA with Unresurfaced Patella - Park, Hyung Jun; Chang, Moon Jong; Kim, Tae Woo; Chang, Chong Bum; Kang, Kee Soo; Kang, Seung-Baik (The Journal of Knee Surgery, 2021)
The degree of cartilage degeneration assessed intraoperatively may not be sufficient as a criterion for patellar resurfacing in total knee arthroplasty (TKA). However, single-photon emission tomography/computed tomography (SPECT/CT) is useful for detecting osteoarthritic involvement deeper in the subchondral bone. The purpose of the study was to determine whether SPECT/CT reflected the cartilage lesion underneath the patella in patients with end-stage osteoarthritis (OA) and whether clinical outcomes after TKA without patellar resurfacing differed according to the severity of patellofemoral (PF) OA determined by visual assessment and SPECT/CT findings. This study included 206 knees which underwent TKA. The degree of cartilage degeneration was graded intraoperatively according to the International Cartilage Repair Society grading system. Subjects were classified into low and high uptake groups according to the degree of bone tracer uptake (BTU) on SPECT/CT in the PF joint. The Feller's patella score and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) were assessed preoperatively and postoperative 1 and 2 years. The increased BTU in the PF joint was associated with more severe degenerative cartilage changes underneath the patella (p < 0.001). The risk for the presence of denudated cartilage was greater in the high uptake group (odds ratio = 5.89). There was no association between clinical outcomes and visual grading of patellar cartilage degeneration or the degree of BTU on SPECT/CT. The visual assessment of the degree of cartilage degeneration underneath the patella and preoperative SPECT/CT evaluation of the PF joint were not predictive of clinical outcome after TKA with unresurfaced patella.
Keywords: patellofemoral joint; single-photon emission tomography; computed tomography; clinical outcome; total knee replacement